2021
DOI: 10.3390/molecules26123502
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of a Promising Antibacterial Agent: 22-(4-(2-(4-Nitrophenyl-piperazin-1-yl)-acetyl)-piperazin-1-yl)-22-deoxypleuromutilin

Abstract: A novel pleuromutilin derivative, 22-(4-(2-(4-nitrophenyl-piperazin-1-yl)-acetyl)-piperazin-1-yl)-22-deoxypleuromutilin (NPDM), was synthesized in our laboratory and proved excellent antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA). In this study, more methods were used to further study its preliminary pharmacological effect. The antibacterial efficacy and toxicity of NPDM were evaluated using tiamulin as the reference drug. The in vitro antibacterial activity study showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The use of Z33 at a dose of 5000 mg/kg with 0.5% CMC-Na did not lead to any significant acute toxicological alterations in the mice. In previous work, many pleuromutilin derivatives were assessed as low toxic compounds with the LD 50 of acute oral toxicity in mice ranging from 2000–3500 mg/kg [ 16 , 17 ]. According to the Globally Harmonized Classification System (GHS) for the classification of chemicals, Z33 was considered a safe and non-toxic compound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Z33 at a dose of 5000 mg/kg with 0.5% CMC-Na did not lead to any significant acute toxicological alterations in the mice. In previous work, many pleuromutilin derivatives were assessed as low toxic compounds with the LD 50 of acute oral toxicity in mice ranging from 2000–3500 mg/kg [ 16 , 17 ]. According to the Globally Harmonized Classification System (GHS) for the classification of chemicals, Z33 was considered a safe and non-toxic compound.…”
Section: Discussionmentioning
confidence: 99%
“…The time–kill kinetics curve of Z33 was determined according to previous reports [ 17 ]. MRSA ATCC 43300 strains were grown in Mueller–Hinton Broth (MHB) at the starting inoculum of 10 6 CFU/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The skin sample exposed to ultrasound with the parameters (the intensity of 0.34 W/cm 2 for 5 min) showed no obvious changes in the skin surface (Supplementary Figure S3). At 2 days after treatment, PDMS slices and surrounding tissues were taken out from the mice for the bacterial count as previously reported (Tang et al, 2021;Zuo et al, 2021). Serum had been taken from the mice before they were sacrificed, and was used for cytokine, liver, and kidney function measurements.…”
Section: Synergistic Therapy With Ultrasound and Drug-loaded Nanopart...mentioning
confidence: 99%
“…7 The increasingly growing multidrug resistance reflects a global issue creating superbugs difficult to treat. 8,9 Moreover, some side effects such as the metal chelation and the retroaction with alkaline drugs also result from the 3-carboxyl group of quinolones. 10−12 It is of great urgency to develop novel therapeutic strategies, antibacterial drugs with high biosafety, and even targets to counteract the growing multidrug resistance in animal husbandry.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is revealed that the bacterial resistance to quinolones might be driven by an increase in the expression of efflux pumps and the decreases of certain outer membrane proteins such as porins as well as the residue mutations of target enzymes in the quinolone resistance determining region, which especially play a vital role in preventing the formation of the ion bridge with 3-carboxyl and 4-carbonyl groups to render quinolones with ineffective antibacterial behavior . The increasingly growing multidrug resistance reflects a global issue creating superbugs difficult to treat. , Moreover, some side effects such as the metal chelation and the retroaction with alkaline drugs also result from the 3-carboxyl group of quinolones. It is of great urgency to develop novel therapeutic strategies, antibacterial drugs with high biosafety, and even targets to counteract the growing multidrug resistance in animal husbandry. , …”
Section: Introductionmentioning
confidence: 99%